Ethnobotanical exploration of medicinal plants in rural populations of the Amazon región - Huanacuni Foraquita, Sosueth (2024)
Ethnobotany emerges as a fundamental field to understand the complex interactions between human communities and local flora, especially highlighting the cultural and medicinal importance of plants. This study focused on documenting traditional knowledge on the use of medicinal plants in the Amazon region, specifically in the districts of La Peca, Amazonas, Peru, during the period from October 2019 to January 2021. The research involved 48 local residents of different ages and genders in La Peca, employing semi-open methods to explore their knowledge about medicinal plants, as well as their uses and methods of preparation. The study documented 113 medicinal plant species in the Amazon region, highlighting Rosaceae, Euphorbiaceae and Rutaceae. Leaves (46.0%) and stems (27.0%) are mainly used, prepared mainly by crushing (52.0%) and cooking (38.0%). Consumption as infusion is common (94.0%), with one-week treatments (54.0%). In conclusion, this study highlights the importance of the Rosaceae, Euphorbiaceae and Rutaceae families in traditional medicine in the region. In addition, it was observed that the diseases treated mainly comprise gastrointestinal and respiratory disorders, along with other common conditions.